ABOUT DIIT-UZ PROFILE OF GRADED-UP FREIGHT WAGONS’ BOGIES EXPERIENCE IN APPLICATION (Transport systems and technologies, 2018)
The reliability of the railway wheels remains the current issue of the railroad yard. Significant funds are spent on the wheels redeployment, which is caused by the wear of the crests. Wheels refacing significantly reduces the wheel's life. Specialists are offered different ways to get out of this situation, namely: the use of wheels made of steel with high carbon content; lubrication; application of various profiles of wheels rolling surface and modernization of running gears. According to the authors, the optimal solution is the modernization of the bogies, while modernized bogies are almost always equipped with wheel pairs with innovative profiles of the wheels rolling surface. Such variants are already implemented and successfully operated on the railways of Ukraine. In the experimental route "Rokuvata-Uzhgorod-Koshice" a separate experimental train was formed that consisted of semi-carriages on the carriages of the model 18-100 without modernization, profile of the rolling surface of the DIIT-UZ wheels and carriages of 18-100 models with modernization of С03-04, profile of the rolling surface wheels DIIT-UZ. During the controlled operation, the cars were under constant control, commission surveys were conducted with the measurement of control parameters. DIIT-UZ profile of graded-up freight wagons’ 18-100 and С03-04 bogies (USA) comparison tests results are presented in this article. Due to data interpretation, depending of wheels run and actual deterioration before and after machining of wheels, average rib’s thickness variation value was obtained. Expected limit of wheels’ wear is presented. The conducted tests confirm that in solving wheel pairs’ wear of the crests problem it is advisable to start with the modernization of existing wheels pairs and the creation of new running parts of rolling stock with constant contact with the slider, since this allows to reduce the wear of the wheels crests significantly. The results of the conducted studies allow us to conclude that the application of the profile of the DIIT-UZ wheels rolling surface in the modernization of the trolleys is effective and reduces the wear of the wheels crests.
Keywords: DIIT-UZ profile, rib’s thickness, actual deterioration